The isolation of a novel inhibitor of adrenal cytochrome P-450 Salsola tuberculata - Swart, P.(Pieter) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.) -- University of Stellenbosch, 1986.